A novel inflammation-based prognostic index for patients with esophageal squamous cell carcinoma: Neutrophil lymphocyte ratio/prealbumin ratio. Issue 7 (February 2019) - Lv, Yajuan; Zhang, Jiandong; Liu, Zhen; Tian, Yuan; Liu, Fengjun
Abstract : Abstract: NLR/Alb (neutrophil lymphocyte ratio/albumin ratio), is a prognostic index for esophageal cancer has been confirmed. Prealbumin (PA) is more sensitive to malnutrition than albumin. A new prognostic index, named neutrophil lymphocyte ratio/prealbumin ratio (NLR/PA), for predicting the survival time in patients with esophageal squamous cell carcinoma (ESCC) was proposed. A retrospective study of 315 cases with ESCC was enrolled. The optimal cut-off values were evaluated by ROC curve (the receiver operating characteristics curve). Pearson correlation analyses were used to calculate the correlations among NLR, Alb, NLR/Alb and NLR/PA. The overall survival (OS) was calculated by Kaplan-Meier method. Cox regression analyses were performed to evaluate the prognostic factors. The optimal cut-off value was 0.01 for NLR/PA according to ROC curve. According to multivariate analyses, TNM stage, NLR, NLR/Alb, NLR/PA were prognostic factors for OS. The AUC area (the area under the receiver operating characteristics curves) of the NLR/PA was higher than the areas of NLR and NLR/Alb for all the patients. The index of NLR/ PA had a higher AUC area than that of the index of NLR or NLR/Alb for patients in stage I-II. But in stage III-IVA, the index of NLR had a higher AUC area than that of the index of NLR/PA or NLR/Alb. The index of NLR/PA is superior to the index of NLR as a prognostic indicator for patients with early stage (stage I-II) ESCC.